Student’s Mathematics Understanding and Learning Outcomes trough Cooperative Learning Model (PRISMA, Prosiding Seminar Nasional Matematika, 2023)
This study aims to determine the student’s mathematic understanding and learning outcomes through the use of cooperative learning models. The method used in this research is literature study through literature review from various sources to strengthen the analysis results. The study of literature in this writing is the basis for the formation of writing as well as a source of writing data based on published journals related to students' mathematics understanding and learning outcomes through cooperative learning models. The results obtained after the analysis showed that there were differences in student’s mathematics understanding and learning outcomes through the use of cooperative learning models. The application of the cooperative learning model can affect the student’s mathematics understanding and learning outcomes by paying attention to the number of students and the material being studied so that the learning process can run effectively. In addition, the use of the cooperative model can stimulate interaction and cooperation between students during the learning process. Suggestions from this research are that further research is needed to determine the effectiveness of the use of cooperative learning models and the comparison of student’s mathematics understanding and learning outcomes using other models.